Oocyte Cryopreservation in Young Women with Low Ovarian Reserve Following Repeated Bilateral Ovarian Cystectomy - Cepi Teguh Pramayadi; Rahmi Isman (Indonesian Socety of Obstetrics and Gynecology, 2026)
Abstract Background: Fertility preservation has become an important aspect for women at risk of diminished ovarian reserve, including patients with ovarian disease. Ovarian cystectomy is known to adversely affect ovarian reserve, particularly after repeated procedures. Oocyte cryopreservation has emerged as an established strategy for preserving fertility potential in such cases. Objective: We report a 23-year-old nulligravid, unmarried, and not sexually active patient with a history of repeated ovarian surgery for managing ovarian cysts. Ovarian reserve testing revealed a markedly reduced anti-Müllerian hormone (0.8 ng/mL), consistent with diminished ovarian reserve. The patient underwent oocyte cryopreservation initiated with controlled ovarian stimulation. Oocyte retrieval yielded three mature oocytes, which were successfully cryopreserved without complication. Consistent with our case, previous studies have shown a 30–50% decline in AMH after cystectomy, with more pronounced effects in bilateral disease or repeated surgery. Although the number of retrieved oocytes was limited, oocyte cryopreservation provided the patient with the possibility of future reproductive options. Conclusion: This case highlights that repeated ovarian surgery can significantly impair ovarian reserve, threatening the future reproductive potential of young women. Although the number of mature oocytes retrieved in patients with diminished ovarian reserve may be limited, oocyte cryopreservation remains an effective strategy to preserve fertility. Keywords: anti-Müllerian hormone, fertility preservation, oocyte cryopreservation, ovarian cystectomy, ovarian reserve, young women.